Strategi Pemasaran Produk Pembiayaan Multi Guna (PMG) Dalam Menarik Minat Nasabah Menabung Di Bank Sumut Syariah Kcp. Lubuk Pakam - Fachri Arrizki, (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The purpose of this study is to raise financing for PT. Bank Sumut Syariah Kcp. Lubuk Pakam had to overcome a number of challenges. The purpose of this study is to pinpoint these issues and learn how banks overcome them. adopting qualitative descriptive techniques in research. Techniques and tools for collecting data include organized interviews and the use of secondary materials from books, journals and other sources. By examining the shortcomings, strengths, opportunities and threats of implementation, this research also uses a data analysis approach for superior ASN Motor Vehicle PMG items